2021
DOI: 10.3389/fspor.2021.658293
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Broadcasting Media Using Social Media Engagement in the WNBA

Abstract: While there has been research into what teams, leagues, and athletes post on social media and the impact of post content on social media engagement, there is limited understanding and empirical research on the impact of broadcasting media on social sport consumption. There are an increasing number of new media through which sport leagues can distribute their content to fans. This research examines the impact of different broadcast platforms on game day engagement with WNBA team Twitter accounts. Using data for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Team sport was the only sport in our study that showed a significant correlation with the motive of social communication on social media. One reason for that could be that, beside few successful (elite) athletes in individual sports, the popularity and (digital) presence of sport teams is comparably high [ 36 ]. Notably, we could not find any correlations between the sport-related use of social media and the motive of self-staging.…”
Section: Discussionmentioning
confidence: 99%
“…Team sport was the only sport in our study that showed a significant correlation with the motive of social communication on social media. One reason for that could be that, beside few successful (elite) athletes in individual sports, the popularity and (digital) presence of sport teams is comparably high [ 36 ]. Notably, we could not find any correlations between the sport-related use of social media and the motive of self-staging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that perceptions around media reporting of mental health drive athlete behaviour (Gulliver et al, 2012), while other research has focused on engagement with sport broadcast platforms in WNBA (Pegoraro et al, 2021). Future research may apply such approaches to also examine the impact of dominant constructions on stigma at an individual level.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, social networks are an excellent tool for fans to proclaim their passion for the team and keep fans active. Furthermore, social networks are characterized by two-way interactive communication, which entails that fans can create content and engagement with the club in question [36]. Responding to a post increases the visibility of the post, and consequently the audience of the team, to a much larger set of consumers than the actual online followers of the team [37].…”
Section: Discussionmentioning
confidence: 99%